2017
DOI: 10.1007/s00018-017-2660-4
|View full text |Cite
|
Sign up to set email alerts
|

TUSC3: functional duality of a cancer gene

Abstract: Two decades ago, following a systematic screening of LOH regions on chromosome 8p22, TUSC3 has been identified as a candidate tumor suppressor gene in ovarian, prostate and pancreatic cancers. Since then, a growing body of evidence documented its clinical importance in various other types of cancers, and first initial insights into its molecular function and phenotypic effects have been gained, though the precise role of TUSC3 in different cancers remains unclear. As a part of the oligosaccharyltransferase com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…In this regard, the cirRNAs ci-ankrd52, ElciEIF3j and circFoxo3 upregulate the expression of their corresponding host genes ANKRD52 [ 30 ], EIF3J [ 31 ] and Foxo 3 [ 22 ]. To assess the potential impact of the circRNAs studied herein upon the linear RNA derived from the host gene, we focused on TUSC3 circ104557 due to the well-recognized feature of its parental gene TUSC3 as a tumor suppressor gene [ 32 ]. To explore its potential activity, we transduced a TUSC3 circ104557 lentiviral expression construct and the empty vector in the colorectal cancer cell lines studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the cirRNAs ci-ankrd52, ElciEIF3j and circFoxo3 upregulate the expression of their corresponding host genes ANKRD52 [ 30 ], EIF3J [ 31 ] and Foxo 3 [ 22 ]. To assess the potential impact of the circRNAs studied herein upon the linear RNA derived from the host gene, we focused on TUSC3 circ104557 due to the well-recognized feature of its parental gene TUSC3 as a tumor suppressor gene [ 32 ]. To explore its potential activity, we transduced a TUSC3 circ104557 lentiviral expression construct and the empty vector in the colorectal cancer cell lines studied.…”
Section: Resultsmentioning
confidence: 99%
“…Of the four identified genes hosting circRNAs that undergo hypermethylation-associated downregulation, only TUSC3 had been previously reported to be epigenetically inactivated in human cancer [ 32 ]. TUSC3 epigenetic loss has been found in colorectal cancer, the same tumor type in which we initiated our screening, and it is associated with adverse prognosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The roles of TUSC3 in cancer progression showed context-dependent manner in several solid tumors. TUSC3 was initially identified as a homozygous deleted gene in metastasized prostate cancer patients and its deficiency upregulated cancer progression and tumorigenesis in ovarian, prostate, glioblastoma and pancreatic cancers 20 24 . However, it has been also reported that TUSC3 was associated with genetic amplification or enhanced cancer progression in head and neck cancer and colorectal cancer 20 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…TUSC3 was initially identified as a homozygous deleted gene in metastasized prostate cancer patients and its deficiency upregulated cancer progression and tumorigenesis in ovarian, prostate, glioblastoma and pancreatic cancers 20 24 . However, it has been also reported that TUSC3 was associated with genetic amplification or enhanced cancer progression in head and neck cancer and colorectal cancer 20 , 25 , 26 . In particular, the controversial observations were reported in TUSC3-dependent oncogenesis in lung cancer 27 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Participants with two copies of the Tumor Supressor Candidate 3, TUSC3 , had a 20% increased odds of pancreatic cancer compared to individuals with germline hemizygous deletions in this gene (90% credible interval (CI) for odds ratio: 1.01 - 1.39). While the direction of this effect is inconsistent with its putative role as a tumor suppressor, up-regulation of TUSC3 and possible oncogenic roles for this gene have been reported in cancers including non-small cell lung cancer, colorectal, thyroid, and head and neck cancers [2427]. Among non-coding regions, we found that deletions for a CNV region in 8q24 were associated with a reduced risk of pancreatic cancer (90% CI: 1.09-1.59).…”
Section: Resultsmentioning
confidence: 99%